PEMANFAATAN BUDAYA LOKAL TORAJA SEBAGAI MEDIA INOVATIF PEMBELAJARAN BAHASA INGGRIS - Elim Trika Sudarsi; Theresyam Kabanga; Yohana Rawina (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The utilization of Toraja local culture as an innovative medium in language learning aims to preserve cultural heritage and enhance understanding of the local language. This activity leverages elements of Toraja culture, such as customs, arts, and language, as engaging learning materials for students. Through this approach, it is hoped that students will find it easier to understand the Toraja language and strengthen their cultural identity. This program also supports the preservation of Toraja culture amid the challenges of globalization